STRATEGI PEMASARAN SEKOLAH DI SMA BATIK 1 SURAKARTA - LESTARI , SRI (2011)
This research is focused on "How is the Marketing Strategy in High School Batik 1 Surakarta" The focus is described into two parts : 1) What are internal and external factors which become the base of the school marketing strategy? ; 2) How is the school marketing strategy according to SWOT matrices analysis? The purposes of this research are : 1) General Purposes : to describe the marketing strategy in High School Batik 1 Surakarta ; 2) Specific purposes : a) to describe the internal and external factors which become the base in the school marketing strategy ; b) to describe the implementation of service marketing diffusion concept 7P in High School Batik 1 Surakarta according to SWOT matrices analysis model. This research is qualitative. The researcher's presence is treated as the research instrument. Primary and secondary data are obtained using data collecting technique of participative observation, depth interview and documentation. The data analysis technique is using interactive model. The analysis process includes three activity, they are data reduction, data service, and drawing conclusion. The results of this research according are as follows : 1) SO strategy is increasing market's segment with promotion, 2) ST strategy is making the human sources to make different product, price, and promotion from the rivals 3) WO strategy is optimizing the use of area for IT-based and characterized learning activities so that it will have loyal customers 4) WT strategy is optimizing the role of human sources to increase the service quality towards the customers. According to the SWOT matrices supported by Reseact and Development data so the most effective school marketing strategy in High School Batik 1 Surakarta is promotion using presentation by the alumnus Junior High School.